Citizens, Network Marketing Communication and Herbal Remedies in Lagos, Nigeria and Lusaka, Zambia - Mercy BANDA; Oscar ODIBOH (Communications of International Proceedings, 2020)
This pilot study examines the citizens’ awareness of the influence of network marketing communication on their usage of herbal medications. Research locations are two African countries; namely, Nigeria and Zambia. In Africa, many people, especially those living in rural countryside, prefer the use of healing herb when faced with health challenges. They assume that herbal medicines are innocuous, active and valuable. However, the reverse is the case in city-centres where documented reports of active use of herbal medications are few. This study was conducted at the same time in Lagos, Nigeria and Lusaka, Zambia to fill this gap. The two cities are metropolitan with fast-growing industrial hubs, dense population, and having high representative margins of the different groups across the countries. A semi-structured questionnaire was administered on 230 respondents in Lagos and Lusaka using the purposive sampling technique. Results show that there is a high awareness of network marketing communication of herbal medications in both countries; although it is stronger in Nigeria than Zambia. Usage of herbal medications in both countries is above par. Similarly, the respondents do not believe that marketing communicators have marginally influenced the citizens to use herbal medications. This study invites collaborations from other parts of Africa and the world at large.
Keywords: Network Marketing; Marketing Communication; Herbal Medications; Citizens; Nigeria; Zambia.